2023
DOI: 10.1111/eci.14095
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world persistence of initial targeted therapy strategy in monotherapy versus combination therapy in patients with chronic inflammatory arthritis

Lorena Exposito,
Carlos Sánchez‐Piedra,
Paloma Vela‐Casasempere
et al.

Abstract: ObjectiveThe persistence of biologic (b) and targeted synthetic (ts) disease‐modifying antirheumatic drugs(DMARDs) in monotherapy versus in combination with conventional synthetic (cs) DMARDs is still a controversial topic in rheumatic diseases. To clarify this issue, the retention of the initial treatment strategy of b/tsDMARD in combination with csDMARD versus monotherapy in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) patients under real‐life conditions was evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“… 3236 38 Recently, a cohort study from the Spanish BIOBADASER III registry demonstrated that combination therapy is associated with lower persistence compared with monotherapy PsA. 39 Furthermore, a recent investigation of cohorts from five different European countries presented inconsistent results of the potential beneficial use of MTX. 40 While a retrospective observational study using data from the US administrative database showed that the therapy with TNFi in combination with MTX was associated with increased persistence of the TNFi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3236 38 Recently, a cohort study from the Spanish BIOBADASER III registry demonstrated that combination therapy is associated with lower persistence compared with monotherapy PsA. 39 Furthermore, a recent investigation of cohorts from five different European countries presented inconsistent results of the potential beneficial use of MTX. 40 While a retrospective observational study using data from the US administrative database showed that the therapy with TNFi in combination with MTX was associated with increased persistence of the TNFi.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no difference in the safety profile between the mono and combination therapy in our study, data from the Spanish registry showed that the addition of a csDMARD to a b/tsDMARD was associated with a significantly worse safety profile than b/tsDMARD monotherapy with infections being the adverse events with the highest increase. 39 …”
Section: Discussionmentioning
confidence: 99%